Steroid-Responsive Large Vessel Vasculitis: Application of Whole-Brain 320-Detector Row Dynamic Volume CT Angiography and Perfusion - Yahyavi-Firouz-Abadi, N. (AJNR Am J Neuroradiol, 2009)
SUMMARY: A patient with suspected giant cell arteritis and prior negative findings on superficial temporal artery biopsy was evaluated with 320-detector row CT angiography (CTA) and whole-brain perfusion. Corticosteroid treatment was initiated on the basis of CT angiography findings of arteritis and a cortical perfusion deficit. The patient's symptoms and perfusion imaging findings resolved following therapy. Whole-brain CTA and imaging was helpful in the diagnosis and monitoring this patient with suspected vasculitis.